Transnational Crime in Money Laundering Cases: An Analysis From the Perspective of Economic Criminal Law - Dwi Nurahman (Journal of Strafvordering Indonesian, 2025)
Money laundering is a transnational crime with significant implications for financial stability and state governance. This study analyzes the enforcement of money-laundering laws in Indonesia through case studies of Rafael Alun Trisambodo and the Bank Indonesia Liquidity Support (BLBI) scandal using a mixed doctrinal and socio-legal approach. Data were collected from statutory analysis, PPATK reports, prosecutorial documents, and scholarly literature. Findings show that despite progressive statutory frameworks, challenges persist in beneficial-ownership transparency, financial-intelligence capacity, and cross-border asset recovery. The Rafael Alun case reflects a family-based laundering scheme, while BLBI illustrates a corporate-state network. This study recommends strengthening PPATK, asset-reporting systems, international cooperation, financial-forensics technology, and the use of non-conviction-based asset forfeiture mechanisms